High quality linked data for stroke obtained using non-government clinical registry and routinely collected hospital and death data - Monique Kilkenny; Joosup Kim; Nadine Andrew; Vijaya Sundararajan; Amanda Thrift; Judith Katzenellenbogen; Felicity Flack; Melina Gattellari; James Boyd; Phil Anderson; Natasha Lannin; Mark Sipthorp; et al. (International Journal of Population Data Science, 2018)
Introduction Recent advances in data linkage infrastructure in Australia mean that data can be linked based on various identifiers across datasets. In a first for Australia, we tested the feasibility of linking data between a clinical quality disease registry with Australian and state government health data across multiple jurisdictions.